THE CONSTRUCTION OF JAVANESE ISLAMIC ETHICS IN SERAT WEDHATAMA: KARL MANNHEIM'S SOCIOLOGY OF KNOWLEDGE APPROACH - Syihabuddin, Muhammad; Mustofa, M. Lutfi; Nurbaiti, Dwi; Wafi, Hasan Abdul (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
As a ruler who contributed to the revival of Javanese culture, especially in literature, Mangkunegara IV is mentioned as a ruler and a poet. One of the largest and most famous of his many literary works is